2021
DOI: 10.1177/17455065211019717
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the Endometriosis and Mental-Health Sequelae; The ELEMI Project

Abstract: Background: It is important to evaluate sequalae for complex chronic health conditions such as endometriosis and mental health disorders. Endometriosis impacts 1 in 10 women. Mental health outcomes can be a primary determinant in many physical health conditions although this is an area not well researched particularly in women’s health. This has been problematic for endometriosis patients in particular, who report mental health issues as well as other key comorbidities such as chronic pelvic pain and infertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Beyond its physical symptoms and body systemic impact, endometriosis presents a substantial comorbidity with mental health symptoms and disorders (Laganà et al, 2015(Laganà et al, , 2017a. Currently, depression and anxiety have been the psychological outcomes most often discussed in the endometriosis literature (Delanerolle et al, 2021). Studies consistently report a higher prevalence of depression in women with endometriosis as compared with other groups.…”
Section: Psychosocial Impact Of Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond its physical symptoms and body systemic impact, endometriosis presents a substantial comorbidity with mental health symptoms and disorders (Laganà et al, 2015(Laganà et al, , 2017a. Currently, depression and anxiety have been the psychological outcomes most often discussed in the endometriosis literature (Delanerolle et al, 2021). Studies consistently report a higher prevalence of depression in women with endometriosis as compared with other groups.…”
Section: Psychosocial Impact Of Endometriosismentioning
confidence: 99%
“…As has been reported in a recent meta-analysis, this effect increases significantly when the comparison comprises exclusively well-matched, healthy controls (Gambadauro et al, 2019). Interestingly, in 2021, another systematic review and meta-analysis reported a prevalence of 28.9% for depression and 31.8% for anxiety (Delanerolle et al, 2021).…”
Section: Psychosocial Impact Of Endometriosismentioning
confidence: 99%
“…Between 1 January 2021 and 30 June 2021, a multicentre cross-sectional study was performed to assess sexual function in a sample of Spanish women diagnosed with endometriosis, using the validated Female Sexual Function Inventory (FSFI) [ 30 , 31 ]. The diagnosis of endometriosis was made in accordance with the guidelines of the European Society of Human Reproduction and Embryology (ESHRE), based on the visual detection of endometriosic lesions during previous surgeries, anatomopathological tests, and typical ultrasonographic features of endometriosis [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite dyspareunia, as well know, plays an important role as an etiologic factor of sexual dysfunction [ 24 , 25 ], which is source of low self-esteem and negative effects on interpersonal relationships [ 22 ], there are other factors not necessarily related to severity of the disease or level of tissue invasion (that include women’s age, mental health, or social or cultural correlates) have been also reported [ 26 , 27 , 28 , 29 , 30 ]. Women with endometriosis report more depression and anxiety symptoms [ 31 ], which might in turn impact sexual function.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation contributes to enhanced sensibility of nociceptive afferents [ 27 ], supporting peripheral and central sensitization processes [ 28 ] in regard to chronic pelvic pain (CPP) as one of the cardinal symptoms [ 1 ]. Overall, the complex pathogenesis might contribute to the existing knowledge gap regarding the precise mental health sequelae of endometriosis and unsubstantiated presumptions about the causality between physical and psychological symptoms [ 29 ].…”
Section: Introductionmentioning
confidence: 99%